PENERAPAN STRATEGI PEMBELAJARAN IPS TERPADU BERDIFERENSIASI DALAM MEMENUHI KEBUTUHAN BELAJAR PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to find out 1) How are the systematic implementation steps of differentiated integrated social studies learning strategies carried out. 2) How does differentiated learning influence various aspects of student’s development. 3) What are the challenges and practical solutions in implementing differentiated instruction in social studies. The research technique used is known as literature review, used to collect information or sources about a particular subject and can be accessed from various sources, including journals, books, the internet, and other literature. The results of the study show that the application of content, process, and product differentiation in Integrated social learning can significantly increase active engagement, intrinsic motivation, self confidence, and student learning outcomes. Comprehensive diagnostic assessment is the main foundation for successful implementationof differentiated learning. Teachers need to have competence in designing flexible learning tools, but still directed towards standardized goals. The implementation of differentiated learning in Integrated social also supports the realization of an inclusive and humanistic.